Realization of a novel free-piston engine generator for hybrid-electric vehicle applications - Smallbone, Andrew; Mohd Razali, Hanipah; Jia, Boru; Scott, Tim; Heslop, Jonathan; Towell, Ben; Lawrence, Christopher; Roy, Sumit; Shivaprasad, K. V.; Roskilly, Antony Paul (American Chemical Society (ACS Publications), 2020)
Free-piston engine generators (FPEGs) have huge potential to be the principal energy conversion device for generating electricity from fuel as part of a hybrid-electric vehicle (EV) powertrain system. The principal advantages lay in the fact that they are theoretically more efficient, more compact, and more lightweight compared to other competing EV hybrid and range-extender solutions (internal combustion engines, rotary engines, fuel cells, etc.). However, this potential has yet to be realized. This article details a novel dual-piston FPEG configuration and presents the full layout of a system and provides technical evidence of a commercial FPEG system’s likely size and weight. The work also presents the first results obtained from a project which set-out to realize an operational FPEG system in hardware through the development and testing of a flexible prototype test platform. The work presents the performance and control system characteristics, for a first of a kind system; these show great technical potential with stable and repeatable combustion events achieved with around 700 W per cylinder and 26% indicated efficiency